2018
DOI: 10.1021/acs.jmedchem.7b01474
|View full text |Cite
|
Sign up to set email alerts
|

Quinazolinone-Based Anticancer Agents: Synthesis, Antiproliferative SAR, Antitubulin Activity, and Tubulin Co-crystal Structure

Abstract: Quinazolinone-based anticancer agents were designed, decorated with functional groups from a 2-methoxyestradiol-based microtubule disruptor series, incorporating the aryl sulfamate motif of steroid sulfatase (STS) inhibitors. The steroidal AB-ring system was mimicked, favoring conformations with an N-2 substituent occupying D-ring space. Evaluation against breast and prostate tumor cell lines identified 7b with DU-145 antiproliferative activity (GI 300 nM). A preliminary structure-activity relationship afforde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 38 publications
3
71
0
Order By: Relevance
“…STX 3451 has a disruptive effect on both the actin and tubulin cytoskeleton leading to the rounding of cells, fragmentation of chromatin and multilobed nucleoli and actin filament disruption. 21 , 32 During this in vitro study, A549 and MDA-MB-231 cells were exposed to the determined GI 50 values of 2-ME, STX 2895, STX 3329, STX 3451 and STX 3450 for 24 h and thereafter stained with anti-tubulin antibodies. Fluorescent microscopy indicated that the compounds resulted in microtubule abrogation and DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…STX 3451 has a disruptive effect on both the actin and tubulin cytoskeleton leading to the rounding of cells, fragmentation of chromatin and multilobed nucleoli and actin filament disruption. 21 , 32 During this in vitro study, A549 and MDA-MB-231 cells were exposed to the determined GI 50 values of 2-ME, STX 2895, STX 3329, STX 3451 and STX 3450 for 24 h and thereafter stained with anti-tubulin antibodies. Fluorescent microscopy indicated that the compounds resulted in microtubule abrogation and DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The sulfamate group is shown to be a mediator of this affinity with β-tubulin, the first example of a sulfamate ester bound to tubulin. Future studies will potentially involve evaluation of this compound in animal models [83].…”
Section: Quinazolinone Derivativesmentioning
confidence: 99%
“…N-heterocycles are important integral pharmacophoric units ubiquitously used in a variety of biologically active natural products, agrochemicals, pharmaceutical and synthetic drugs (Khan et al, 2016). 2,3-Dihydroquinazolin-4(1H)-one plays an important role in the aromatic nitrogen-containing heterocycles because of their abundant pharmacological and biological activities (Kshirsagar, 2015;Zawawi et al, 2015;Dohle et al, 2018). Compounds containing this motif have shown significant biological activities which include anticancer, anticonvulsant, antidefibrillatory, analgesic, diuretic, antihistamine, antihypertensive, and many other activities (Patil et al, 2015;Zawawi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%